6(b-4)-5(b+4)=6

Simple and best practice solution for 6(b-4)-5(b+4)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(b-4)-5(b+4)=6 equation:


Simplifying
6(b + -4) + -5(b + 4) = 6

Reorder the terms:
6(-4 + b) + -5(b + 4) = 6
(-4 * 6 + b * 6) + -5(b + 4) = 6
(-24 + 6b) + -5(b + 4) = 6

Reorder the terms:
-24 + 6b + -5(4 + b) = 6
-24 + 6b + (4 * -5 + b * -5) = 6
-24 + 6b + (-20 + -5b) = 6

Reorder the terms:
-24 + -20 + 6b + -5b = 6

Combine like terms: -24 + -20 = -44
-44 + 6b + -5b = 6

Combine like terms: 6b + -5b = 1b
-44 + 1b = 6

Solving
-44 + 1b = 6

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '44' to each side of the equation.
-44 + 44 + 1b = 6 + 44

Combine like terms: -44 + 44 = 0
0 + 1b = 6 + 44
1b = 6 + 44

Combine like terms: 6 + 44 = 50
1b = 50

Divide each side by '1'.
b = 50

Simplifying
b = 50

See similar equations:

| 12c-8c= | | X=8z-3y | | 18h=12 | | 4x+80=-6 | | 11m+3n-4m+9n= | | 2X-2=36 | | 8x-9=-2x+11 | | 2x^3+5x^2-16x+9=0 | | 12x+18=10x | | 6x+32=16x-48 | | 3x*3y=-1 | | 2x-3y=28 | | 4(3m+4)=(6m+8) | | 128a^3+686j^3=0 | | i+6i=0 | | (x-4)*(2x-3)=2x*2x | | -(7y+1)-(-6y-5)=3 | | 4x^2-y^2-8x-10y-25=0 | | -8n+4(1+5n)=-6n | | 4t-16+8y=-4 | | -4n-40=79-2n+2 | | -8n+4(2+5n)=-6n-14 | | 7a-3=4+6a | | y=(1/2)/(6/18) | | 9x^2+24x+9=0 | | 90-(5x+10)=90-(x+2) | | 5x^2+x-10=0 | | 63-3x=11-9x | | 0x+11=71-3x | | 5x-94=2x-7 | | 4x-8-2x=x-2 | | 5(4-3)=19 |

Equations solver categories